2022
DOI: 10.1186/s13756-022-01166-z
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and the risk of catheter-related bloodstream infection: a systematic review and meta-analysis

Abstract: Background The role of obesity in catheter-related bloodstream infection has been reported in several studies, but it is still controversial. We conducted this meta-analysis to summarize existing evidence to assess the relationship between obesity and the risk of catheter-related bloodstream infection. Methods We searched MEDLINE, EMBASE, PubMed and Web of Science for the related studies published before January 2022. Meta-analysis was performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…Although obesity is a well-recognized risk factor for deep venous thrombosis (DVT) and CVC-related thrombosis in adult patients with cancer, 30 as well as for CRBSIs, 31 this study found no association of an overweight condition with a higher risk for CVC-related thrombosis or CRBSI in children with solid cancers. Part of this observation is based on the findings of Abate et al, 22 who suggest that there is no reason to consider overweight children or adolescent cancer patients at higher risk for DVT, which is different from what is generally stated for adult cancer patients.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Although obesity is a well-recognized risk factor for deep venous thrombosis (DVT) and CVC-related thrombosis in adult patients with cancer, 30 as well as for CRBSIs, 31 this study found no association of an overweight condition with a higher risk for CVC-related thrombosis or CRBSI in children with solid cancers. Part of this observation is based on the findings of Abate et al, 22 who suggest that there is no reason to consider overweight children or adolescent cancer patients at higher risk for DVT, which is different from what is generally stated for adult cancer patients.…”
Section: Discussioncontrasting
confidence: 75%
“…The finding of the recent study that underweight children had slightly more complications compared to other BMI categories is in contrast to the study conducted by Wang et al, who observed no association between underweight and Hickman-related complications, particularly with CRBSI. 31 A proposed mechanism underlying this underweight paradox is that pediatric malignancy results in a malnourished state, manifested as weight loss accompanied by deficits in immune system function, tissue maintenance, and other processes potentially responsible for Hickman-related complications. This finding could also be explained by the fact that clustering is a normal phenomenon in small random and pseudo-random data samples.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that the incidence of infection and adverse events increased in patients with obesity or overweight, compared with counterparts with a normal BMI ( Mathison, 2003 ; Olsen et al, 2008 ). In a previous meta-analysis, overweight was significantly associated with increased risk of catheter-related bloodstream infection (OR = 1.43, 95% CI [1.12–1.82]) ( Wang et al, 2022 ). Al-Shaiji & Radomski (2012) reported that patients with a BMI of 30 or more showed a higher incidence of urinary mixed leakage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis focusing on ICU patients revealed that high BMI was independently associated with an increased risk of CLABSI. 21 In contrast, in elderly patients over the age of 75, low BMI has been identified as a risk factor for the development of infections and mortality. 22 , 23 Research conducted among patients with COVID-19 demonstrated that individuals with a lower BMI exhibited an elevated susceptibility to developing secondary infections.…”
Section: Discussionmentioning
confidence: 99%